Teachers’ Experience in Times of Pandemic with Students with Educational Challenges: Challenges in Returning to Face-To-Face Education with an Inclusive Approach in Medellín, Colombia - Correa-Alzate, Jorge Iván (2023)
Objective. This article aims to analyze how 63 primary education teachers who have worked on the inclusion process with students presenting educational challenges in the visual (image processing), cognitive (concrete action processing), and communicative (viso-gestural processing for Colombian Sign Language-LSC users) fields in Medellín, assumed home education during the 2020-2021 pandemic. Method. This qualitative research work with an interpretive approach utilized the focus group technique, organizing the teachers into three groups based on the students’ educational challenges: visual, cognitive, and communicative. The analysis focused on the teachers’ approach to home education, the strategies they used, and their decision-making processes in terms of orienting learning, considering the challenges that this group of students faces in their learning styles. Data were analyzed using selective open coding and axial coding. Results. The results were grouped into six moments of home education through which the teachers passed, which were disorientation, forced landing, adaptation, cooperation, expansion, and return. Each moment had its characteristics, successes, and failures during the experience. Conclusions. The teachers’ experience during the pandemic was closest to remote education rather than home education, characterized by mistakes influenced by low knowledge in cognitive accessibility and the use of ICT platforms, orientation to families lacking or with low accessibility in connectivity, and successes in collaborative networking among teachers and the academic community to discuss teaching and evaluation practices in inclusive education. The findings in each moment experienced by the teachers during the pandemic were used to project the challenges in education with the students that focus on challenges at the socioemotional level, in learning, teaching, family support, and teacher training in the return to face-to-face education.